Choice between Domestic Debt and Foreign Debt: Evidence from Pakistan - Sheikh, Muhammad Ramzan; Farooq, Fatima; Zulifiqar, Salyha (2017)
The developing countries are facing huge budget deficits. This paper aims to explore the important dimension of deficit financing.It is imperative to investigate whether the government should rely on domestic debt or foreign debt.This study has used the time series data from 1972 to 2016 by applying the ARDL approach.The findings of the study point out that the stock of domestic debt is more beneficial than the foreign debt while foreign debt servicing is harmful for economic growth.